(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, it is reflected that the selection of methods in the process of practical training in the teaching of technology is considered one of the most important tasks, if the appropriate method is chosen incorrectly, the joint activity of the teacher and the student will be ineffective, and the selection of new methods of teaching is carried out based on certain principles.